TEACHING ENGLISH BASED ON 2013 CURRICULUM AT JUNIOR HIGH SCHOOL IN GOWA - Zohra Inayah Nasir (Universitas Islam Negeri Alauddin Makassar, 2015)
The objective of this study was to describe the ability of teachers in four piloting schools in applying the 2013 curriculum. It was conducted at four piloting junior high schools in Gowa. This research consisted of four samples, and researcher used the purposive sampling. The data were collected by using observation sheet in observing the teacher’s mastery toward the learning concept based on 2013 curriculum, teachers’ ability in constructing the lesson plan as recommended by 2013 curriculum, the teachers’ ability in applying the scientific approach at class, and teachers’ ability in assesing based on 2013 curriculum rules. In analyzing the data, researcher used descriptive quantitative. After analyzing the data, it was found that the teachers’ understanding about 2013 curriculum in teaching English are very good with the SMPN 1 Bontomaranu’s score is 90, SMPN 3 Sungguminsa’s score is 91, SMPN 1 Sungguminasa’s score is 92, SMPN 1 Pallangga’s score is 94. Therefore, the researcher suggested to the teacher who have been observed to sustain their ability about 2013 curriculum and also spread their ability to the other teacher who did not really understand yet about the 2013 curriculum for better English teaching and education in Gowa.